2022
DOI: 10.28945/4900
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral Care in Doctoral Education: A Collaborative Autoethnography of Belonging and Academic Identity

Abstract: Aim/Purpose: It is increasingly recognized that doctoral education programs should better support doctoral students. In particular, it has been noted that students experience significant isolation during their PhD, which negatively affects their educational experiences and their personal wellbeing. Doctoral writing groups are collaborative learning communities that have in recent years received increasing attention to address this issue. This collaborative autoethnography explores the affective benefits (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…I have found that my writing group students often develop signi cant friendships and that these friendships become supportive academic networks when the students graduate. These types of support networks have been shown to allow students to share their struggles, build a sense of belonging, and gain emotional support (see, e.g., Hradsky et al, 2021). This helps my writing group students develop e cacy and resilience during their studies.…”
Section: Insights and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…I have found that my writing group students often develop signi cant friendships and that these friendships become supportive academic networks when the students graduate. These types of support networks have been shown to allow students to share their struggles, build a sense of belonging, and gain emotional support (see, e.g., Hradsky et al, 2021). This helps my writing group students develop e cacy and resilience during their studies.…”
Section: Insights and Recommendationsmentioning
confidence: 99%
“…There are many educational strategies that help foster community, including collaborative learning. Writing groups, as a type of collaborative learning community, have been shown to foster students' academic identity, sense of belonging, academic writing skills, and ability to learn through purposeful re ective practice (Cahusac de Caux et al, 2017;Chakraborty et al, 2021;Hradsky et al, 2021;Lam et al, 2019). I have found that my writing group students often develop signi cant friendships and that these friendships become supportive academic networks when the students graduate.…”
Section: Insights and Recommendationsmentioning
confidence: 99%
“…One particular type of peer engagement that is featured in this study but is currently quite underreported in the literature (Cahusac de Caux, 2021), is the potential of virtual writing retreats to enable students to work productively with others in motivating social settings. Writing groups, in any form, constitute a powerful learning practice that enhances collaboration, academic identity, a sense of belonging, feedback, and productivity (Chakraborty et al, 2021;Hradsky et al, 2021). Furthermore, when these networks open up opportunities for the students to publish their work, positive shorter and longer-term outcomes can ensue, such as successful degree completion and ulterior academic advancement as part of a future career in research (Larivière, 2012).…”
Section: Figure 7 Psychological Capital -Meta-theme Arising From the ...mentioning
confidence: 99%
“…Where there is less emphasis on the departmental mission, students will tend to adopt mastery-orientated learning goals and will seek self-improvement through more individualized socialization. To create the latter environment, there needs a proactive effort from the faculty and department (Hradsky et al, 2022). This complex institutional dynamic can confuse new students, especially those who are acculturating.…”
Section: Acculturative Stress Intersects With Academic Identity Devel...mentioning
confidence: 99%